2018
DOI: 10.1002/mnfr.201800134
|View full text |Cite
|
Sign up to set email alerts
|

Diet during Pregnancy is Implicated in the Regulation of Hypothalamic RNA Methylation and Risk of Obesity in Offspring

Abstract: We propose the regulatory capacity is now broadened for the first time to include m6A in developmental programming and obesity phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It is generally believed that when m 6 A RNA is methylated, demethylase FTO will play a role after methylated transferase ( Mathiyalagan et al, 2019 ). Recent studies have correlated changes in m 6 A levels with human reproductive disorders ( Kaspi et al, 2018 ). Given that the m 6 A modification occurs at the 3’-UTR near the transcription termination site ( Lan et al, 2019 ), accumulation of hypermethylated mRNAs due to aberrant FTO expression during SA likely affects the expression levels of crucial genes.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that when m 6 A RNA is methylated, demethylase FTO will play a role after methylated transferase ( Mathiyalagan et al, 2019 ). Recent studies have correlated changes in m 6 A levels with human reproductive disorders ( Kaspi et al, 2018 ). Given that the m 6 A modification occurs at the 3’-UTR near the transcription termination site ( Lan et al, 2019 ), accumulation of hypermethylated mRNAs due to aberrant FTO expression during SA likely affects the expression levels of crucial genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that m 6 A RNA methylation even played an essential role in fetal developmental programming (Kaspi et al 2018). Maternal diet can regulate fetal programming through m 6 A RNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Metabolic Syndrome, including type 2 diabetes mellitus (T2DM) and depression, is associated with disturbances of circadian rhythms, most studies of these diseases use nocturnal mice and rats whilst modelling diurnal humans. A diurnal, well-accepted and extensively studied model for T2DM [48,51,[100][101][102][103] is the sand rat, (Psammomys obesus). When the sand rats are fed normal rodents chow they develop T2DM characterized by enhanced insulin secretion and insulin resistance at the early stages and insulin deficiency at an advanced stage [100,102].…”
Section: Boxmentioning
confidence: 99%
“…It is noteworthy that these epigenetic modifications can be transmitted intergenerationally. For example, studies in Psammomys obesus have shown parental diet regulates DNA and RNA methylation and the expression of genes implicated with the increased risk of obesity in offspring .…”
Section: Introductionmentioning
confidence: 99%